THE CONTRIBUTION OF THE SCHOOL OF AERONAUTICAL SCIENCES OF TAUBATÉ TO THE FORMATION OF HUMAN CAPITAL FOR THE LOCAL AERONAUTICAL INDUSTRY - Silva, Dimas Lucas Lara da (2022)
The purpose of this work is to analyze and highlight the importance of the contribution of the Municipal School of Aeronautical Sciences (EMCA) of Taubaté to the formation of human capital for the local aeronautical industry. It was also aimed to explore and highlight the performance of the aeronautical sector in the Metropolitan Region of the Paraíba Valley and North Coast and its relevance to local development. The methodology used in this research was a bibliographic review addressing the topic of regional development and analysis of quantitative data obtained by the Law of Access to Information and public qualitative data, comparing these data with the information in the bibliography in order to perform a conclusive analysis of this information.